"It's Just Too Much": The Financial Calculus in Medicare Hospice. Issue 2 (May 2023) - Cabin, William
There is extensive literature on the significance of financial incentives in the Hospice Medicare Benefit (HMB) and the growth of proprietary ownership of hospices in the United States. A literature review indicates a paucity of information on hospice nurses' and hospice social workers' perceptions of the impact of the HMB's financial structure on care planning and delivery decisions. In a previous issue of this journal, the author addressed the literature gap by presenting a study on hospice nurses' perceptions of the impact of financial factors on their decision-making regarding care for Medicare hospice beneficiaries. The study presented in this article is a companion qualitative study to the nurses' study. This article presents background on the topic and an initial, exploratory study to address the literature gap, based on interviews of a convenience sample of 37 hospice social workers from 6 different hospices between December 1, 2018 and January 31, 2020, in the New York City metropolitan area. Six themes emerged from the interviews: finances are the guiding principle in care planning and service delivery decisions; balancing patient care needs, cost, and finance-related length of stay (LOS) is a challenge; the emphasis on finance diminishes the social workers' ability to address hospice patient needs; the emphasis on finance diminishes the social workers' ability to address hospice caregiver needs; the social work role is diminished because of the role of nurses in developing and implementing the plan of treatment, which influences finances; and the Interdisciplinary Team (IDT) is the crucial clinical and financial decision-making setting, but gives limited weight to social work input.